A rare case of double pituitary prolactinomas: the diagnostic application of intraoperative ultrasonography and DNA methylation markers - Jared C. Reese; Thomas M. Zervos; Jack Rock; Abeer Tabbarah; Houtan Noushmehr; Grayson Herrgott; Ana Valeria Castro (Archives of Endocrinology and Metabolism)
SUMMARY The aim of this study is to describe the management and evolution of a patient with the rare condition of double lactotroph tumors and assess the role of intraoperative ultrasonography (IOUS) for their detection and methylation-based liquid biopsy for their diagnosis and monitoring. A 29-year-old woman diagnosed with double lactotroph tumors through hormonal and MRI workup underwent surgical resection due to cabergoline intolerance. To detect a tumor missing through visual inspection, IOUS was performed. Pituitary tumor (PT) and nontumor (NT) tissues and blood were collected for pathological and molecular assessments (genome-wide methylation level profiled using the EPIC array, at surgery and follow-up). Reference methylome data were obtained from publicly available repositories. Both tumors (T1 and T2) were detected via IOUS and confirmed as lactotroph tumors through immunohistochemistry. In tissue specimens, PT-specific markers distinguished T1 from NT tissue, while T2, primarily nontumor cells, clustered with NT specimens. In liquid biopsies, these markers differentiated between T and NT cohorts. During the 12-month follow-up, methylation profiling and prolactin blood assessments showed that methylation markers clustered with NT specimens, which coincided with prolactinemia normalization, indicating successful tumor control after surgery. This case illustrates the translational use of methylation-based liquid biopsy methodologies in detecting and monitoring PTs through the detection of tumor-specific markers in blood specimens. This approach can be useful to distinguish sellar masses mimicking PTs based on nonspecific imaging features and to monitor for early recurrence of PTs, particularly nonfunctioning PTs lacking specific biochemical markers. This case also illustrated the role of IOUS in identifying multiple PTs missed by visual inspection alone, leading to improved patient outcomes through complete tumor resection.